Oxygen uptake kinetics and biomechanical behaviour at different percentages of VO2max - Sousa, A.; Figueiredo, P.; Ribeiro, J.; Silva, A.; Cascais, C.; Pelarigo, J.; Vilas-Boas, J. P.; Fernandes, R. J. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Sustaining exercise beyond a few seconds depends upon the appropriate supply and utilisation of oxygen (Jones and Poole 2005). However, the kinetics of oxygen uptake (V02 ) response to exercise depends on its intensity, being described three main exercise intensities- moderate, heavy and severe (Gaesser and Poole 1996)-and more recently, a fourth much less studied one- extreme (Hill et al. 2002). The V02kinetics at moderate and heavy exercise intensities is well documented in the literature, namely in treadmill running and cycle ergometer exercise (Sousa et al. 2011b; Burnley and Jones 2007). To date, the investigation of V02 kinetics in swimming has been limited either by the use of specific competitive distances (Rodriguez et al. 2003; Sousa et al. 2011b; Sousa et al. 2011a) or by presenting the V02 slow component as the only kinetic parameter of the V02 response (Demarie et al. 2001; Fernandes et al. 2003). The purpose of this study was to compare the V02kinetics and biomechanical responses in three time to exhaustion exercises from rest to different percentages of maximal oxygen uptake (V02max) intensity- 95, 100 and 105%.